Maxillary Alveolar Ridge Expansion with Split-Crest Technique Compared with Lateral Ridge Augmentation with Autogenous Bone Block Graft: a Systematic Review - Thomas Starch-Jensen; Jonas Peter Becktor (Stilus Optimus, 2019)
Objectives: The objective of the present systematic review was to test the hypothesis of no difference in implant treatment outcome after maxillary alveolar ridge expansion with split-crest technique compared with lateral ridge augmentation with autogenous bone block graft. Material and Methods: A MEDLINE (PubMed), Embase and Cochrane Library search in combination with a hand-search of relevant journals was conducted. Human studies published in English until 8th of February, 2018 were included. Results: One comparative and four noncomparative studies fulfilled the inclusion criteria. Both treatment modalities disclosed high survival rate of implants with few complications. High survival rate of prosthesis, implant stability values, limited peri-implant marginal bone loss and gain in maxillary alveolar ridge width were reported with the split-crest technique. Patient-reported outcome measure and length of patient treatment time was not assessed in any of the included studies. Conclusions: The split-crest technique seems to be useful for horizontal augmentation of maxillary alveolar deficiencies with high survival rate of prosthesis and implants. However, further long-term randomized controlled trials with larger patient sample as well as assessment of patient-reported outcome measures and patient treatment time are needed before well-defined conclusions can be provided about the two treatment modalities.